Capnography monitoring reduces incidence of hypoxia in older patients undergoing gastrointestinal endoscopy under propofol sedation - Lian, Qiuyue; Wu, Jianbo; Zhang, Jie; Zhang, Yizhe; Cheng, Xiangyang; Yang, Xiaomei; Zhou, Renlong; Chen, Yue; Ding, Weiwei; Wang, Guangzhi; Yu, Weifeng; Zhang, Jiaqiang; Su, Diansan (Endoscopy International Open, 2025)
Whether routine capnography monitoring during gastrointestinal endoscopy sedation can reduce occurrence of hypoxia is controversial. Older patients are more prone to hypoxia. This study aimed to determine the effect of additional capnography monitoring on incidence of hypoxia in older patients undergoing gastrointestinal endoscopy under propofol sedation.A multicenter, randomized, single-blind, two-arm, parallel-group, controlled with an active comparator, interventional superiority clinical trial was performed at three teaching hospitals in China between September 1, 2021, and September 1, 2022. This study compared additional capnography monitoring (intervention group) and standard monitoring (control group) among older patients (aged 65–79 years) undergoing gastrointestinal endoscopy under propofol sedation. The primary outcome was incidence of hypoxia (75%-89% for < 60s). Secondary outcomes were incidence of subclinical hypoxia (90%-94%), incidence of severe hypoxia (< 75% for any duration or 75%-89% for ≥ 60s), and other adverse events (AEs).Data from 1777 participants (888 intervention, 889 control group) were analyzed. Additional capnography monitoring reduced incidence of hypoxia in older patients from 19% to 12% (P < 0.001). Incidence of subclinical hypoxia in the additional capnographymonitoring group was 23% and in the standard monitoring group was 15% (P < 0.001). There was no significant difference in incidence of severe hypoxia (P = 0.070) and other AEs between the two groups (P = 0.374).Additional capnography monitoring during gastrointestinal endoscopy for older patients who were sedated with propofol reduces incidence of hypoxia.
Keywords: Quality and logistical aspects; Sedation and monitoring; Quality management; Performance and complications